Au/BiPO4 nanorod catalysts: synthesis, characterization and their catalytic performance for CO oxidation. Issue 19 (5th February 2016) - Zhang, Ping; Yu, Huanhuan; Li, Jingjing; Zhao, Hang; Zhu, Baolin; Huang, Weiping; Zhang, Shoumin
Abstract : Au/BiPO4 catalysts exhibit high catalytic activity in low temperature CO oxidation. Abstract : In this paper, monoclinic phase BiPO4 nanorods were successfully prepared by a one-pot solvothermal route. Au/BiPO4 catalysts were obtained by a deposition–precipitation method. The samples were characterized by X-ray diffraction, transmission electron microscopy techniques, energy dispersive X-ray analysis, X-ray photoelectron spectroscopy, and UV-vis diffuse reflectance spectroscopy. The TEM results exhibited a good dispersion of gold nanoparticles over the support. The XPS spectra revealed that gold was in the metallic state and bismuth was in the +3 oxidation state. The catalysis results demonstrated that BiPO4 nanorods could be a good support for gold catalysts. Among the prepared catalysts, the 1.5% Au/BiPO4 pretreated at 300 °C showed the best performance in CO oxidation and could achieve 100% CO oxidation at 40 °C. It retained 100% conversion after continuous operation for 10 h at 40 °C, and showed no deactivation after 50 h at a selected high reaction temperature of 180 °C. The possible mechanism of Au/BiPO4 catalysts in the CO oxidation was also proposed.